EVALUASI IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSI PADA SATUAN PENDIDIKAN DASAR DI INDONESIA DALAM PERSPEKTIF KEBIJAKAN PUBLIK - Sutrisno, Nisa Wening Asih; Taufiqurokhman, Taufiqurokhman; Rakinda, Oman Rohman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study is to assess the degree to which inclusive education policies have been used in Indonesian primary education units, pinpoint difficulties and barriers, and provide a scholarly contribution to the field of public administration studies, specifically with regard to the application of education policies. The study used a qualitative methodology and a literature review technique, critically examining government papers, policy documents, regulations, and other studies. The research was restricted to the conceptual and policy levels through the use of a literature review, which strengthened the theoretical knowledge and analytical foundation for the implementation of inclusive education policies. The findings show that while Indonesia has a solid legislative foundation for inclusive education, there are still a number of obstacles to overcome before it can be implemented in primary schools. Planning, organization, execution, and supervision are areas where disparities occur. Teachers lack the necessary pedagogical skills to work with pupils who have special needs, the inclusive organizational structure has not been developed adequately, and policy distribution has not been divided equally. Additionally, the quality of inclusive services is deteriorated by a lack of facilities, a tight budget, and social stigma.. Through a public governance approach that highlights the connection between policy design, institutional capability, and social dynamics in the context of primary education, this study strengthens the viewpoint of inclusive education policy implementation. The study's findings support the idea that Indonesia's problems with inclusive education stem not just from a lack of funding but also from a lack of ability to integrate policies and implement them across sectors. Therefore, attaining effective, equitable, and sustainable inclusive education requires interagency collaboration, strengthening governance, and methodically increasing teacher capacity.